PENGARUH KUALITAS LAYANAN DAN PENANGANAN KELUHAN TERHADAP RETENSI NASABAH DALAM PERSPEKTIF INTERMEDIASI KREDIT PADA PRODUK KUR BRI UNIT PARUNG BOGOR - Rizkika Cahya Anggraini; Iman Lubis (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the influence of service quality and complaint handling on customer retention from the perspective of credit intermediation in the Kredit Usaha Rakyat (KUR) product at BRI Unit Parung Bogor. Customer retention in this research reflects the continuity of financing relationships, the tendency to apply for repeated financing, and the stability of customers in maintaining their credit commitments—all of which are closely related to the effectiveness of credit intermediation at the unit level. This study employed a quantitative approach by distributing questionnaires to KUR customers and analyzing the data using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination.The results indicate that service quality has a positive and significant effect on customer retention, and complaint handling likewise shows a positive and significant effect. Simultaneously, service quality and complaint handling significantly influence customer retention, as evidenced by an F-value of 72.584 with a significance level of 0.000. This demonstrates that both variables collectively contribute strongly to increasing customer retention in KUR financing. High customer retention directly enhances the effectiveness of credit intermediation by improving repayment smoothness, reducing the risk of non-performing loans, and increasing the likelihood of customers reusing financing services.These findings emphasize that improving service quality and enhancing the professionalism of complaint handling are crucial strategies for BRI Unit Parung Bogor in strengthening customer retention and supporting sustainable credit intermediation within the microfinance sector.